(untitled) (Al-Qamar, 2025)
The dominant perceptions about the Islamists are that of rigid, uncompromising and anti-democratic actors. The objective of this article was to ascertain the reality behind such claims. A case in point is Jamāt-e-Islāmī Pakistan (JI) which is blamed for its tactical support to the authoritarian regime of General Mohammad Zia-ul-Haq during the years 1977-88, and resultantly being labelled as an anti-democratic force. Prominent works authored by distinguished scholars were explored to ascertain the reality behind this claim. One-to-one interviews were also conducted to cross-verify the facts. The party’s decisions during this period were analytically reviewed with the help of background context. This study found that the main concerns of the party during the Zia period were the implementation of Nizam-e-Mustafa as demanded by the anti-Bhutto movement, early elections and avoidance of any confrontation with state institutions. When the party realized that the methods adopted by the incumbent regime contradicted JI’s vision, the party stalwarts started criticizing the regime. Due to the Afghan issue and the previous experience of the Bhutto regime, the party did not join the opposition movement led by Pakistan Peoples Party. However, the party vehemently opposed the dictatorial stance of Zia’s sympathizers in the higher courts. Resultantly, criticism of the military regime costed the party in the form of the neutralization of its student organization (Islāmī Jamiat-e-Talaba) and the dismissal of its city government of Karachi. Based on these facts, claiming the Islamists as being non-democratic falls short of being convincing proofs. The study transpired that JI, through a pragmatic approach, has continuously tried to synthesise Islamic politics with democratic norms as per its own understanding.